Creación de una operadora turística y el desarrollo socioeconómico en la ciudad de Quevedo, año 2019 - Cedeño Pincay, Francisca Jesus (2020)
Tourism is a worldwide phenomenon, which continues to generate a strong economy; THIS also serves as a development engine for the various national economic sectors, among them we have the tour operators whose function is to serve as a link to facilitate the access of tourists in the country or region. The research work carried out on the feasibility study for the creation of a tour operator that meets the recreation needs of the inhabitants of the Province of Los Ríos Canton of Quevedo. The interaction of the economy and sustainability is therefore sought, thus improving the quality of life of all its inhabitants. For this reason, the research proposes the creation of a tour operator where the public and private sector are involved to meet the demands of the population and generate NEW sources of income and local development of the area. For the development of the research process, methods, techniques and resources that allowed the scientific development of the work have been used, so the analytical, deductive, inductive method was used and the techniques used were the observation and the bibliographic collection and the survey.